Chemistry the molecular science - Moore, John W.; Stanitski, Conrad L. (Cengage Learning, 2015)
This book features a problem-solving methodology, a revision of its award-winning art program to help students visualize chemical processes at a molecular level, and an integrated coverage of organic and biochemistry content.